Social-structural contexts of needle and syringe sharing behaviours of HIV-positive injecting drug users in Manipur, India: a mixed methods investigation - Shunmugam Murali; Newman Peter A; Chakrapani Venkatesan; Dubrow Robert (BMC, 2011)
Abstract Background Few investigations have assessed risk behaviours and social-structural contexts of risk among injecting drug users (IDUs) in Northeast India, where injecting drug use is the major route of HIV transmission. Investigations of risk environments are needed to inform development of effective risk reduction interventions. Methods This mixed methods study of HIV-positive IDUs in Manipur included a structured survey (n = 75), two focus groups (n = 17), seven in-depth interviews, and two key informant interviews. Results One-third of survey participants reported having shared a needle/syringe in the past 30 days; among these, all the men and about one-third of the women did so with persons of unknown HIV serostatus. A variety of social-structural contextual factors influenced individual risk behaviours: barriers to carrying sterile needles/syringes due to fear of harassment by police and "anti-drug" organizations; lack of sterile needles/syringes in drug dealers' locales; limited access to pharmacy-sold needles/syringes; inadequate coverage by needle and syringe programmes (NSPs); non-availability of sterile needles/syringes in prisons; and withdrawal symptoms superseding concern for health. Some HIV-positive IDUs who shared needles/syringes reported adopting risk reduction strategies: being the 'last receiver' of needles/syringes and not a 'giver;' sharing only with other IDUs they knew to be HIV-positive; and, when a 'giver,' asking other IDUs to wash used needles/syringes with bleach before using. Conclusions Effective HIV prevention and care programmes for IDUs in Northeast India may hinge on several enabling contexts: supportive government policy on harm reduction programmes, including in prisons; an end to harassment by the police, army, and anti-drug groups, with education of these entities regarding harm reduction, creation of partnerships with the public health sector, and accountability to government policies that protect IDUs' human rights; adequate and sustained funding for NSPs to cover all IDU populations, including prisoners; and non-discriminatory access by IDUs to affordable needles/syringes in pharmacies.